2020
DOI: 10.1002/wea.3867
|View full text |Cite
|
Sign up to set email alerts
|

Simulated impact of global warming on extreme rainfall events over Cameroon during the 21st century

Abstract: Spatial distribution of the seasonal changes (in %) between future and historical periods (2021–2050 minus 1981–2010); for total wetday rainfall amount (PRCPTOT; first row), wet‐day frequency (RR1; second row), wet‐day intensity (SDII; third row), dry spells (CDD; fourth row) and total wet‐day rainfall above the 95th percentile (R95PTOT; fifth row), from RCM ensemble mean experiments over Cameroon. Stippling indicates areas where the change is significant (i.e. where at least 80% of simulations agree on the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…It follows a spatio-temporal variability of precipitation as well as a northward migration of dry isohyets. These observations are in agreement with findings in [8]. A systematic low SDII was obtained in the northernmost part of Cameroon with values below 7 mm.…”
Section: Spatial Variability Of Extreme Indicessupporting
confidence: 93%
See 1 more Smart Citation
“…It follows a spatio-temporal variability of precipitation as well as a northward migration of dry isohyets. These observations are in agreement with findings in [8]. A systematic low SDII was obtained in the northernmost part of Cameroon with values below 7 mm.…”
Section: Spatial Variability Of Extreme Indicessupporting
confidence: 93%
“…A number of recent studies [6] highlight the necessity for consideration of using dynamically downscaled regional climate models (RCMs), such as those from the Coordinated Regional Climate Downscaling Experiment Program (CORDEX) to analyze extreme trends. Results of [7] and [8] revealed that the RCMs used in their study mimic quite well the spatial distribution of precipitation extremes. Rainfall extreme changes have been explored in many regions in Africa [9]; they showed some significant trends in heavy precipitation over Central Africa.…”
Section: Introductionmentioning
confidence: 90%
“…Data limitations and observation station sparsity are still a commonly cited concern for many researchers in the years 2013-2020 (see Tables S1-S11) for a full list of relevant publications citing this limitation). The lack of a spatially extensive, high-temporal resolution observation network has limited the attempts to evaluate the impacts of climate change in several societal domains when utilizing simulation outputs from Global Climate Model (GCM), often embedded in the Coupled Model Intercomparison Project (CMIP); as well as Regional Climate Model (RCM), carried out within the framework of the COordinated Regional Climate Downscaling Experiment (CORDEX) initiative [29,33,34,[42][43][44][45]. The latter authors noted that the lack of precipitation-related variables in mountainous regions may lead to interpolation errors.…”
Section: Resultsmentioning
confidence: 99%
“…Information at a regional scale is highly desirable, particularly across the African continent, for practical planning of local issues, such as rain-fed agriculture, water resources availability, and flood management. Often, challenges in acquiring adequate data for the modelling task at hand and the spatial distribution of the data may render certain analyses impossible; for instance, on accounting for small geographic areas with high topographical variability, see [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The area featuring high and very high agricultural drought hazards are distributed in most parts of the study domain [10]. In addition, the total wet-day rainfall amount above the 95th percentile is projected to consistently increase (by about 10-15%) during the first half of the century in the study area [20]. Based on this analysis, there is a clear and present need to aggregate cotton yield and climate data from different regions, perhaps with more detailed management information, to provide a much-needed observational constraint on projections of both climate change and management impacts on future food security.…”
Section: Discussionmentioning
confidence: 99%